2013
DOI: 10.1590/0104-1169.2970.2375
|View full text |Cite
|
Sign up to set email alerts
|

The hospitalized preterm newborn: The significance of parents' participation in the Neonatal Unit

Abstract: OBJECTIVE: to identify and analyze the significance of participation for parents in a Neonatal Unit (NU) of a maternity hospital in San Luis Potosí, Mexico. METHOD: a qualitative study with 20 parents of both sexes, between 18 and 39 years of age, with a preterm hospitalized child. A content analysis using a thematic approach was used for information processing. RESULTS: the significance of: a) the NICU as a place of suffering and waiting, b) dealing with the child's admittance, c) being excluded from the hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 9 publications
1
30
0
9
Order By: Relevance
“…Findings in a qualitative study showed that the hospital system does not allow the fathers to have access to the NU because they consider them as a vehicle of infections [20] . In developed countries, studies have shown that there is a gender difference with respect to participation [22] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Findings in a qualitative study showed that the hospital system does not allow the fathers to have access to the NU because they consider them as a vehicle of infections [20] . In developed countries, studies have shown that there is a gender difference with respect to participation [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Staff must also consider the parents' feelings, including the therapeutic aspects of mourning management. Parents' experiences in the NU involve suffering and hope when coping with the hospitalization of their child, along with satisfying the child's and their own emotional needs, as shown in qualitative studies from México, China and Australia [20,25,26] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After this stage, we did a transversal reading, seeking to identify the units of meanings that were grouped into two empirical categories. 15 Prior to the field work, the research was approved by the Research Ethics Committee of the Federal University of Minas Gerais, according to opinion of number 0339.0.203.000-11. The anonymity of the participants was guaranteed by coding their names (C1, C2, etc.)…”
Section: Methodsmentioning
confidence: 99%